Exploiting lstm Algorithm for renewable energy - ferhat, adel; toumi, salsabil (جامعة الوادي University of Eloued, 2019)
"استهلاك الطاقة المتزايد في السنوات الأخيرة المبني على استخراج البترول، بات على وشك النهاية، وعليه فإنه في المقابل تزايد الاهتمام بالطاقات المتجددة، التي جذبت الكثير من الأبحاث في هذا المجال من أجل توفير طاقة آمنة وكافية للمستهلك. وعلى اعتبار أن إنتاج الطاقة المتجددة لا يزال غير كافي بالنسبة للاستهلاك من جهة، ومن جهة أخرى، ارتباطه الوثيق بحالة الطقس أو الطبيعة، لذلك بات من الضروري معرفة ما مدى قدرتنا على التنبؤ بإنتاج الطاقة المتجددة مستقبلا، وهو الأمر الذي يشكل تحديا باعتباره غاية في الأهمية بالنسبة للاستهلاك البشري اليومي. في هذا العمل، استخدمنا مصادر الطاقة المتجددة، والألواح الشمسية، ومنابر الرياح مع تكنولوجيا إنترنت الأشياء لنقل بيانات وخصائص الطاقة المولدة ومن ثم التعلم العميق. من أجل اقتراح بنية للتنبؤ بالطاقة تتكون من ثلاث وحدات رئيسية، وحدة استخراج البيانات، وحدة تخزين البيانات، وحدة تعلم الآلة، نقترح فيها خوارزمية ذاكرة طويلة المدى ثم مقارنتها بثلاثة نماذج لتوضيح قوة نظامنا الذي لديه القدرة والأفضلية للتنبؤ بحجم إنتاج الطاقة مع تحسين وقت التنفيذ.""Increased energy consumption in recent years based on oil extraction is about to end. Therefore, in contrast the growing interest in renewable energies, (never ending), has attracted a lot of research in this area in order to provide safe and adequate energy to the consumer. As renewable energy production is still insufficient for consumption, on the other hand, it is closely related to weather or nature, so it is necessary to know how much we can predict future renewable energy production, which is challenging as it is very important for daily human consumption. In this work, we used renewable energy sources, solar panels and wind tribunes with the Internet of things (IoT) technology to transfer the data and characteristics of energy generated and then deep learning. In order to propose an architecture to energy forecasting composed of three main modules, data extraction module, data storage module, machine Learning Module, in which we suggest a Long Short-Term Memory (LSTM) algorithm and compared it with three models to illustrate the power of our system that has the ability and preference to predict the size of energy production with the optimization of execution time ."
mémoure master informatque
Keywords: التنبؤ بالطاقة المتجددة، إنترنت الأشياء، التعلم العميق، الذاكرة طويلة قصيرة -الأجل.; Renewable Energy forecasting, Internet of Things, Deep learning, Long Short-Term Memory.